Legislating Respect: A Pro-Choice Feminist Analysis of Embryo Research Restrictions in Canada - Deckha, Maneesha (McGill Law Journal / Revue de droit de McGill, 2012)
This article investigates the impact of legislating respect and dignity for the embryo in vitro on the legal and cultural status of the embryo in utero. It evaluates the restrictions on embryo research in Canada’s Assisted Human Reproduction Act (AHRA) to consider whether they should receive pro-choice feminist support. Specifically, the article explores whether it is possible for feminists to accord respect to the in vitro embryo, as the AHRA attempts to do, without jeopardizing support for abortion. The article canvasses the theoretical possibilities of this position by comparing the compatibility of feminist articulations of a right to abortion (bodily integrity and equality) with feminist arguments against the expansive use of embryos in research (commodification and exploitation). The article argues that it is logically compatible for feminists to promote “respect” and “dignity” for in vitro embryos while maintaining a pro-choice position on abortion. The article nevertheless cautions against feminist support for AHRA as it currently stands given that, on a practical basis, a feminist understanding of the AHRA’s restricted embryo research regime is difficult to achieve in the public sphere. The article explains why the more likely result for the public sphere will be an unqualified discourse of respect and dignity for embryos in general, which could then problematically revive the abortion debate and destabilize the non-personhood status of the in utero embryo. As a remedy, the article provides recommendations for how AHRA should be amended so as to better ensure that legislative restrictions on embryo research signal a legislative intent that respects women’s reproductive autonomy.